DEVELOPING A SUSTAINABLE CHARACTER EDUCATION MANAGEMENT MODEL FOR INTEGRATED ISLAMIC ELEMENTARY SCHOOLS - Sakban, Sakban; Syahrullah, Muhammad; Salman, Salman; Lisman, Muhammad (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Existing educational institutions should be run for the educational objectives mandated by Law No. 20 of 2003. There are several aspects that will be influenced by the objectives, namely curriculum design, teaching methodology and graduate output. Purpose: The urgency of this research is to meet the needs of the JSIT Association (Integrated Islamic School Network) of Riau Province and regulators in this case the Pekanbaru City Education Office. A model is needed. On the other hand, technology is also an important part in building a sustainable model. The purpose of this research is to provide empirical evidence in the form of recommendations for acceptable models (stakeholders), which can be applied according to the character of SD IT. Method: The method used in this research is the mix method with an economic and Malay cultural approach, then interactive and integrative are carried out in an effort to maintain sustainability. Result: The results show that the model is acceptable, implementable, profitable and sustainable. This is built on the principles of Integrative, Social, Character, Productive and Sustainable so it can be called the IS-KPB Model (Integrated, Social, Character-Based, Profitable, Sustainable). Conclusion: This model is then used as a guideline for curriculum design, school management systems, and strengthening networks between schools and the wider community.